Cursos técnicos computacionais: um modelo de trabalho entre conceitos e frameworks de mercado - Felicio Filho, Antonio (2024)
The paper presents an analysis of professional technical education in Information and Communication Technology (ICT) in Brazil, highlighting its historical evolution, current challenges, and future opportunities. Initially, it addresses the historical context of technical courses in the country, emphasizing the importance of technical training since the beginning of the 20th century and its relevance in Brazil's industrial and technological development. The research focuses on the curricular structure and teaching methodologies adopted in technical institutions, with a special focus on the Federal Institute of Education, Science, and Technology of São Paulo (IFSP). It examines how the computer science technical curriculum aligns with market demands, incorporating both theoretical and practical knowledge, and discusses the need for constant updating in the face of rapid technological changes. One of the main challenges identified is the high rate of dropout and student disengagement in technical courses. The work proposes strategies to tackle these problems, such as the adoption of frameworks in the educational process, the integration of project-based learning practices, and the proposal of partnerships with companies in the ICT sector. It highlights the importance of pedagogical approaches that increase student engagement, such as gamification and the use of advanced educational technologies. It is also suggested that educational institutions should promote an education that goes beyond technical competencies, emphasizing the development of social skills and civic education. It concludes that for the future of technical education in ICT in Brazil, continuous adaptation to technological advances and the needs of students is essential, thus ensuring the training of qualified professionals adaptable to the dynamics of the job market